Letter (copy) : Sandals and socks for Spain - Tewson, Vincent
030-0124-001 Secretary's. HVT/FC/499. EXPORT ST/GH 1179. 6th July,1938. Mr. E. Winstanley, The Co-operative Wholesale Society Ltd., 1, Balloon Street. MANCHESTER, 4. Dear Mr. Winstanley, SANDALS AND SOCKS FOR SPAIN. I thank you for your letter of the 4th instant containing an extract from a letter from your Works. I note their comments and also the fact that the sandals and socks are being despatched from Garston to Rouen tomorrow. As soon as we receive your account for this shipment it shall have immediate attention. Yours sincerely, Assistant Secretary. 292/946/30/124